Glycolytic inhibition and calcium overload as consequences of exogenously generated free radicals in rabbit hearts. - Corretti, M C (1991)
Free radicals have been implicated in the pathogenesis of reperfusion injury, but it is unclear how they exert their deleterious effects on cellular metabolism. Several lines of indirect evidence suggest that free radicals elevate intracellular Ca2+ concentration ([Ca2+]i) and inhibit glycolysis as part of their mechanism of injury. We tested these ideas directly in hearts subjected to hydroxyl radicals produced by the Fenton and Haber-Weiss reactions. Nuclear magnetic resonance spectra were obtained from Langendorff-perfused rabbit hearts before, during, and after 4 min of perfusion with H2O2 (0.75 mM) and Fe(3+)-chelate (0.1 mM). Isovolumic left ventricular pressure exhibited progressive functional deterioration and contracture after exposure to H2O2 + Fe3+. Phosphorus nuclear magnetic resonance (NMR) spectra revealed partial ATP depletion and sugar phosphate accumulation indicative of glycolytic inhibition. To measure [Ca2+]i, fluorine NMR spectra were acquired in a separate group of hearts loaded with the Ca2+ indicator 5F-BAPTA [5,5'-difluoro derivative of 1,2-bis-(o-aminophenoxy)ethane- N,N,N',N'-tetraacetic acid]. Mean time-averaged [Ca2+]i increased from 347 +/- 14 nM in control to 1,026 +/- 295 nM 4 min after free radical generation (means +/- SEM, n = 7), and remained elevated thereafter. We conclude that free radicals induce clear-cut, specific derangements of cellular metabolism in the form of glycolytic inhibition and calcium overload. The observed increase in [Ca2+]i suggests that the deleterious effects of free radicals are at least partially mediated by secondary changes in cellular calcium homeostasis.